SIMPUS eHealth Evaluation at Bantul District, Yogyakarta - Lusiana Wiwid Endriani; Sulistyawati Sulistyawati (Universitas Muhammadiyah Yogyakarta, 2019)
Indonesia government through Indonesia Ministry of Health has developing Health Information System, including Primary Health Care Information System Management (SIMPUS), as a tool to acquire an accurate data to improve society health quality. SIMPUS has been implemented in several districts in Indonesia, including Bantul District, Yogyakarta. But, founded several problems during the implementation. This research aimed to evaluate SIMPUS eHealth implementation compared to IHIS. Qualitative with case study approach was used to capture the data in Piyungan Public Health Centre. PIECES was employed as an evaluation method. Our respondents were SIMPUS manager, SIMPUS officer in mother and child health, SIMPUS officer in patient registration, and SIMPUS officer in the medical record. Our research revealed that eHealth was powerfull than IHIS. Nevertheless, there were several limitations on eHealth such as less of control-security and service. For future research suggested to include more number of Puskesmas as a sample to figure out the comprehensive problem.